International management : culture, strategy, and behavior - Doh, Jonathan P.; Luthans, Fred (New York : McGraw Hill LLC, 2023)
"The global business environment in recent years has been characterized by substantial and often unforeseen change. By some accounts, the degree of uncertainty and volatility in global political and economic affairs has increased as several long-term trends have come to a halt or, in some cases, reversed. Political conflicts, economic disruptions, and realignment of security arrangements have all created challenges for global business. Around the world, support for global economic integration and engagement appears to be on the decline. The vote by the United Kingdom to separate from the European Union and the withdrawal of the United States from the Trans-Pacific Partnership, a proposed trade agreement among 12 Pacific-facing nations, are two stark examples of this broad trend. Some see the United States as retreating from its long-held position as the leading advocate of trade and economic interdependence. Further, trade tensions have risen not just between the U.S. and China, two world powers jockeying for global leadership, but also between the U.S. and its key allies, such as the European Union and Canada. Concurrently, nationalist sentiments in the United States, Europe, Asia, and elsewhere have resulted in raised barriers to both legal and illegal immigration. Exacerbating these pressures, longstanding concerns about the uneven impacts of globalization on jobs, wages, and incomes have resurfaced, as have broader questions about the costs of economic globalization to both developed and developing countries and their citizens"--
Revised edition of International management, [2021]
Includes bibliographical references and index.
Keywords: International business enterprises -- Management; International business enterprises -- Management -- Case studies